Victor Arnautoff and the Politics of Art - Cherny, Robert W. (Book collections on Project MUSE., 2017)
Victor Arnautoff, an artist, was born in 1896 in the Russian empire. After serving as a cavalry officer in WWI and then in the White Siberian army during the Russian Civil War, he became part of the Russian diaspora, working for a Chinese warlord, studying art in San Francisco, and working with Diego Rivera in Mexico. This text examines his life and work.